Structural, electronic, mechanical, and thermodynamic properties of ultra-high-temperature ceramics α- and β-YAlB4: A first-principles study. Issue 7 (1st April 2021) - Zhang, Jinpeng; Bao, Longke; Kong, Zhuangzhuang; Wang, Renfu; Duan, Yonghua; Qi, Huarong; Peng, Mingjun
Abstract: In this work, we performed first-principles calculations to study the structural, electronic, mechanical, and thermodynamic properties of α - and β -YAlB4 . α - and β -YAlB4 was an ultra-high-temperature ceramic. α -YAlB4 belonged to the type of YCrB4, the space group was Pbam, β -YAlB4 belonged to the type of ThMoB4, and the space group was Cmmm . The bulk modulus B, Young's modulus E, and shear modulus G of YAlB4 in the (100), (010), and (001) planes were calculated, and the results revealed that the elastic modulus of YAlB4 had obvious anisotropy. An analysis of state density showed that YAlB4 was a ternary metal boride that had the properties of metal, and the chemical bond was the combination between covalent bonds and metal. We also discuss the minimum thermal conductivity of α - and β -YAlB4 using Clark and Cahill's models. The dynamic stability of YAlB4 was verified by the phonon dispersion curve.